COMPARATIVE STUDY REGARDING THE FUNCTIONAL AND SOMATIC DEVELOPMENT IN 10-11-YEAR OLD CHILDREN FROM DIFFERENT GEOGRAPHICAL REGIONS FROM ROMANIA (Fiep Bulletin - online, 2013)
Every person's health is influenced by the health of the environment: each individual affects the environments he/she lives in. The environment represents all the biotic (relations established within a population/species, or between different species), and abiotic factors (geographical factors - geographical position, expressed through latitude, longitude, altitude, exposition; physical factors - light, temperature, humidity; chemical factors - substances in the air, water, soil). Thus, one can observe the existence of an inverse proportionality between the level of industrialization and the state of the environment. Through their structure, placements, and function, the large cities exert a great pressure on the environmental factors, and implicitly, on the comfort and state of health of the population. All of the other anthropic activities generate various polluting substances that influence the quality of the environmental factors; in this context one can give as example the pollution produced by industrial activities, population-generated wastes and used waters, pollution from transportation vehicles, noise pollution, and accidental pollutions.This paper will present comparative assessments between two distinct Romanian regions, Bra?ov and Bac?u. The two cities were chosen because the comparative research regarding the influence of geographical regions on the main somatic and functional parameters was conducted in them.
Keywords: study; functional and somatic development; 10-11-year old children.